PEMBERDAYAAN MASYARAKAT MELALUI PENDEKATAN KELOMPOK (Kasus Pemberdayaan Masyarakat Miskin melalui Pendekatan Kelompok Usaha Bersama (KUBE) - Joyakin Tampubolon; Basita Ginting Sugihen; Margono Samet; Djoko Susanto; Sumardjo Sumardjo (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2006)
Department of Social affairs implemented several empowerment programs to eradicate poverty. KUBE was one of these poverty eradication programs. KUBE was infended to over-come the group weaknesses through mutual and cooperative efforts. In this relation there were some factors affecting the KUBE dynamic i.e., member characteristics, empowerment patterns, and the KUBE social environment. To optimize the KUBE empowerment, the KUBE productive business activities were classified into three categories, namely daily income, monthly income and annual income earning activities.